Hemodialysis Outcome at Rasheed Shekoni Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:The growing number of patients with Chronic Kidney Disease (CKD) is alarming. This is particularly so in developing countries where glomerulonephritis and unknown causes are common in addition to the rising incidence of hypertension and diabetes. Hemodialysis is the common Renal Replacement Therapy (RRT) modality worldwide; however, many ESRD patients in developing countries cannot sustain hemodialysis beyond few months. We review the experience of a new hemodialysis center in a developing country to highlight the indications and outcome of hemodialysis.Materials and Methods:We retrospectively reviewed the case files and dialysis charts of all patients that had hemodialysis at Rasheed Shekoni Specialist Hospital over the first two years.Result:A total of 96 patients were dialyzed in the center during the two years. Fifty-seven were males and 22 were businessmen. The mean age was 39.19 ± 16.9 years, females were slightly younger. Seventy one of the patients had CKD while 25 had Acute Kidney Injury (AKI). Males had significantly higher serum urea and calcium, while the females had significantly higher serum albumin. More than half of the patients with CKD could not afford hemodialysis beyond the first 6 weeks. At the end of two years only one patient was still on dialysis, 3 patients were referred for kidney transplantation while the remaining patients had discontinued dialysis after an average of 8 weeks.Conclusion:The discontinuation rate of hemodialysis due to ESRD is high in developing countries. This is mostly due to the high cost of hemodialysis and relatively few centers that are concentrated in urban areas. The government has to develop policy to subsidize hemodialysis as well as develop other RRT modalities such as peritoneal dialysis and transplantation.